Analisis Kritis Penerapan Pidana Kebiri Kimia Dalam Sistem Pemidanaan di Indonesia - Lukman Hakim; Endang Hadrian; Anggreany Haryani Putri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
The issuance of Law Number 17 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection which among others regulates new provisions, namely the heavier punishment for offenders of sexual crimes against children, namely the death penalty, life imprisonment, and a maximum sentence of death penalty. 20 years in prison and additional penalties in the form of announcing the identity of the perpetrator and punishment for actions in the form of chemical castration and the installation of electronic detectors, it turns out that there are many problems, especially those related to chemical castration. The problem of chemical castration in the world of medicine and psychology and the problem of chemical castration in the perspective of criminal law are one of them. Therefore the study uses normative research method and carried out by using the statutory approach through a review of laws and regulations as well as regulations relating to the issue discussed. Legal materials are obtained from Undang-Undang Nomor Undang-Undang Nomor 17 Tahun 2016 concerning Child Protection and the Criminal Procedure Code (KUHAP), and in addition, the secondary legal materials are obtained from books, journals and other literature. Meanwhile, the data collection technique used is a library research by examining legal materials relevant to the research discussion.